Preparation and characterization of mesoporous bioactive glass from agricultural waste rice husk for targeted anticancer drug delivery. Issue 2 (1st February 2017) - Chen, Shiow-Yi; Chou, Po-Fong; Chan, Wai-Kong; Lin, Hsiu-Mei
Abstract: Mesoporous bioactive glass (MBG) possesses excellent biocompatibility and an important material used for bone regeneration and drug delivery. The aim of this study is to synthesize MBG from low-cost agricultural waste rice husk (rMBG) using a sol-gel process. We show that rMBG has typical characteristics of the well-ordered hexagonal mesostructure of MBG and can be grafted with folic acid (FA) and then loaded with anticancer drugs for targeting cancer cells. By loading rMBG-FA with camptothecin (CPT, a water-insoluble anticancer drug) we formed rMBG-FA/CPT, which killed cancer cells by being selectively and efficiently taken in via the cells' FA receptors (FRs). We found that rMBG-FA/CPT showed a higher cytotoxicity to FR-overexpressed HeLa cells than to FR-deficient L929 cells. Our results indicate that low-cost rMBG offers a potentially practical medical application that can replace highly valuable MBG as well as reduce environmental pollution caused by agricultural waste.